Politik in Demokratien ohne demokratischen Souverän: Das Scheitern der demokratischen Konsolidierung in Mittelamerika - Tangermann, Klaus-Dieter (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 1996)
In the last years the consolidation of the central American democracies did not succeed because the usual symbolic forms of political behaviour in consolidated democracies did not correspond to the traditional participatory modes of political articulations in Central America. Without the institutional recognition of these forms of participation representation of the interests of the poor majorities remain excluded from the sphere of political decision.